2020
DOI: 10.1155/2020/4205640
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effects of Plasma-Activated Medium Produced by a Microwave-Excited Atmospheric Pressure Argon Plasma Jet

Abstract: Cold atmospheric plasma (CAP) has been reported to have strong anticancer effects in vitro and in vivo. CAP has been known to induce apoptosis in most cancer cells by treatment to cells using direct and indirect treatment methods. There are many reports of apoptosis pathways induced by CAP, but for indirect treatment, there is still a lack of fundamental research on how CAP can cause apoptosis in cancer cells. In this study, we applied an indirect treatment method to determine how CAP can induce cancer cell de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 58 publications
2
31
0
Order By: Relevance
“…Most of the reactive species found in the liquid phase are either primarily generated in the gas phase and at the gas-liquid interface or are the end-products of the transformation of primary ROS/RNS in liquid [30,31,38,39]. While H 2 O 2 is a central player in the anti-cancer capacity of CAP treatment [40][41][42][43][44][45][46][47][48][49], we, and others, have shown that H 2 O 2 and NO 2 − act synergistically to induce cell death after plasma treatment [46,50,51].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the reactive species found in the liquid phase are either primarily generated in the gas phase and at the gas-liquid interface or are the end-products of the transformation of primary ROS/RNS in liquid [30,31,38,39]. While H 2 O 2 is a central player in the anti-cancer capacity of CAP treatment [40][41][42][43][44][45][46][47][48][49], we, and others, have shown that H 2 O 2 and NO 2 − act synergistically to induce cell death after plasma treatment [46,50,51].…”
Section: Introductionmentioning
confidence: 99%
“…While several groups have shown that, in vitro, both treatments were equivalent in inducing cancer cell death, in altering cell surface adhesion molecules or in inactivating enzymatic functions [46,[56][57][58], others have reported that direct treatment is more effective than indirect treatment at killing tumor cells [59][60][61][62][63]. Moreover, there is still a debate regarding the selectivity of cold plasma at inducing cell death preferentially in tumor cells over healthy cells [46,49,[64][65][66][67][68][69][70][71]. These discrepancies between reports can be attributed to the fact that the anti-cancer capacity of plasma-activated liquid depends on several factors such as the size of the wells in which cells are seeded, the volume of the treated liquid, the liquid composition (e.g., PBS versus culture medium), the gap between the plasma source and the liquid, the gas flow rate, the gas admixture, and the plasma device itself [48,[71][72][73].…”
Section: Introductionmentioning
confidence: 99%
“…Different types of human fibroblasts were used in studies and it was shown that the treatment with PAM was better tolerated than the direct plasma treatment [38]. PAM activated by He plasma jet decreased the Nuff fibroblasts viability by 20% [39] and 3T3 fibroblasts, if PAM was activated for more than 30 seconds [40]. PAM activated by Ar plasma reduced the viability of WI-38 by 40% [26], however, it had no effect on mammary epithelium cells [41] or human astrocytes [24].…”
Section: Discussionmentioning
confidence: 99%
“…During cell/tissue treatment with CAP or PAM, cellular and organelles membranes represent the natural interphase, which first comes in contact with the above mentioned RONS produced in PAM or within the cells. The membranes allow for the translation of RONS chemical reactivity into distinct biological responses [ 38 ]. Tumour cells are protected against intercellular apoptosis by inducing signalling with increased expression of membrane-associated enzymes catalase and superoxide dismutases [ 39 ].…”
Section: Intercellular Effects Of Reactive Species Generated By Camentioning
confidence: 99%
“…The exposure to CAP or PAM initially inactivates only a small percentage of protective membrane-associated catalase molecules in the tumour cells [ 28 ]. Then the tumour cells efficiently propagate their cell death through their own CAP-induced RONS signalling [ 38 , 44 ].…”
Section: Intercellular Effects Of Reactive Species Generated By Camentioning
confidence: 99%